Fatores determinantes da aplicação do conhecimento específico de jovens futebolistas - Reis, Marcos Antônio Mattos dos (2016)
Specific knowledge of soccer players consists in solving capacity of problems arising from the complex interplay of environment, unpredictable and chaotic, emerging from the interaction between tactics and technique. The tactic is the game space management capabilities from tactical behaviors come from tactical principles. The technique consists of specific motor skills primarily made with the ball and that materialize the player's game intelligence. Psychosocial and biological factors may influence in a direct way the formation and development of specific knowledge of football players. Thus, this thesis consisted of four studies, although independent, sought in association verify the effects of these factors on manifestation of specific knowledge in young footballers. Briefly, the studies aimed at answering the following questions: a) Wich is the leadership profile of football coaches of Aracaju youth teams? b) Do players born in the first months of the year have different tactical behavior of those born in recent months? c) Somatic maturation and motor age influence the tactical behavior in young players? d) The proportion of use of preferred and non-preferred foot (technical functional asymmetry) in the technical actions affects the tactical behavior in young players. We evaluated the tactical behavior, the use of preferred and non-preferred foot, and releases by analyzing game. Coaches from Aracaju feature profile of autocratic leadership, positive reinforcement and training-education. The tactical performance was not influenced by month of birth, level of maturity, the motor age or technical functional asymmetry, although the tactical efficiency was partially influenced. A sample of 22 coaches and a total of 152 players from teams that competed in the Youth Championships in 2015, promoted by Sergipe Football Federation. The leadership profile of the coaches was determined by the Revised Leadership Scale for Sport. Tactical behavior and technical functional asymmetry were assessed by match-analysis, under FUT-SAT and SAFALL-FOOT protocols, respectively. The relative age was stratified into four-month periods based on month of birth. Somatic maturation was identified from the distance (in years) of each player from peak growth rate. Finally, the motor age was established by battery Lincoln-Oseretsky tests. Coaches from Aracaju feature predominantly autocratic style of decision, and high positive reinforcement and training-education. Tactical performance was not influenced by the relative age, somatic maturation level, the motor age nor technical functional asymmetry, although the tactical efficiency was partially influenced.